Religious and Non-Religious Narratives on Migration : Interdisciplinary Perspectives - Polak, Regina, (Religion and Transformation in Contemporary European Society ;, 2025)
This volume analyzes religious and non-religious narratives on migration from an international and interdisciplinary perspective. Narratives shape the perception of migration. The recourse to religion as well as the self-understanding of religious people and religious communities play an important role in this context. As part of the COST Action 2017 "Connecting Theory and Practical Issues of Migration and Religious Diversity", international researchers from various disciplines - theology, social sciences, philosophy - are exploring contemporary perspectives on migration based on subject-specific understandings of the concept of "narrative" and are also discussing the role and contributions of religion. Particular attention is paid to the original voices of migrants. For this purpose, the innovative method of so-called "narrative cafés" was developed. The volume thus offers numerous insights for critical reflection on migration narratives in academic and socio-political practice.